A Study on the Influence of the Ancient Indian Gurukul System on Modern Education: प्राचीन भारत की गुरुकुल प्रणाली का आधुनिक शिक्षा पर प्रभाव का अध्ययन - Kumar, Ravindra (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The ancient Indian Gurukul system was not only a medium of education but also a cultural, moral, and spiritual framework that worked to develop students in a holistic manner. In this system, education was not confined to bookish knowledge; it encompassed the art of living, social responsibilities, moral values, and comprehensive self-development. In today’s modern education system—where technology, digital tools, competitive examinations, and professional success are emphasized—certain concepts of the Gurukul system still remain alive and play a significant role in guiding modern education. In the Gurukul system, the relationship between teacher (guru) and student (shishya) was deeply sacred and personal. Education was imparted at the guru’s ashram or residence, where students would learn by serving the guru, staying close to him, and absorbing his experiences. This relationship was not limited to the transfer of knowledge; it was also a lesson in life philosophy, discipline, self-restraint, and reverence. In today’s educational system, the student–teacher relationship has become more formal. However, ongoing efforts to reintroduce moral and value-based education reflect the renewed relevance of the Gurukul system. Abstract in Hindi Language: प्राचीन भारत की गुरुकुल प्रणाली न केवल शिक्षा का माध्यम थी, बल्कि यह एक सांस्कृतिक, नैतिक और आध्यात्मिक संरचना भी थी, जिसने विद्यार्थियों को संपूर्ण रूप से विकसित करने का कार्य किया। इस प्रणाली में शिक्षा केवल पुस्तकीय ज्ञान तक सीमित नहीं थी, बल्कि यह जीवन जीने की कला, सामाजिक जिम्मेदारियों, नैतिक मूल्यों और आत्मविकास का समग्र प्रशिक्षण थी। आज के आधुनिक शिक्षा प्रणाली में जहाँ तकनीक, डिजिटल उपकरण, प्रतिस्पर्धात्मक परीक्षा और व्यावसायिक सफलता पर ज़ोर है, वहीं कहीं-न-कहीं गुरुकुल प्रणाली की अवधारणाएँ अब भी जीवित हैं, और आधुनिक शिक्षा को दिशा देने में महत्वपूर्ण भूमिका निभा रही हैं। गुरुकुल प्रणाली में गुरु और शिष्य के बीच का संबंध अत्यंत पवित्र और आत्मीय होता था। शिक्षा गुरु के आश्रम या निवास स्थान पर दी जाती थी, जहाँ छात्र गुरु की सेवा करके, उसके निकट रहकर, उसके अनुभवों से सीखते थे। यह शिक्षण संबंध केवल ज्ञान के हस्तांतरण तक सीमित नहीं था, बल्कि यह एक जीवन-दर्शन, अनुशासन, संयम और श्रद्धा का पाठ भी सिखाता था। आज की शिक्षण प्रणाली में छात्र-शिक्षक संबंध औपचारिक हो गया है, लेकिन नैतिक शिक्षा और मूल्य-आधारित शिक्षा के पुनर्स्थापन की जो कोशिशें हो रही हैं, वे गुरुकुल प्रणाली की पुनर्प्रासंगिकता को दर्शाती हैं। Keywords: प्राचीन भारत, गुरुकुल प्रणाली, आधुनिक शिक्षा, व्यावसायिक सफलता, नैतिक मूल्य, पुस्तकीय ज्ञान